Post-Transition Investment Behavior in Poland : A Sectoral Panel Analysis - Murgasova, Zuzana (IMF Working Papers; Working Paper ;, 2005)
Analyzing and projecting the behavior of macroeconomic variables in new EU member states presents special challenges, owing to limited time series of the available data. This paper presents an analysis of investment in Poland based on an underexplored sectoral data set. The determinants of investment are found to include lagged investment, lead production, relative unit labor costs, EU demand, corporate profitability, and greenfield FDI (foreign direct investment) inflows. Dynamic in-sample simulations indicate some overinvestment in 1997 compared with what the model would suggest, and a substantial underinvestment during 2000-2004. The model is then used to project future investment: while rapid investment growth is likely, it remains uncertain whether investment as a share of GDP will reach its peak levels on the late 1990s.